Respiratory index of severity in children score for assessment of severity in pediatric pneumonia- a hospital-based study - Verma, Ekta; Das, Indira; Das, Anupam (International Journal of Research in Medical Sciences, 2023)
Background: This hospital-based study aimed to evaluate the respiratory index of severity in children (RISC) score’s performance in predicting severity and mortality risk in pediatric pneumonia patients in a developing nation. Methods: The study included 200 children under 5 years of age who were admitted to the ward and pediatric intensive care unit (PICU) and did not have documented congenital heart disease, chronic respiratory illness, congenital lung problems, immunosuppressive conditions, or known neuromuscular disorder with respiratory system involvement. The RISC score was determined, and its correlation with chest x-ray score, mortality, and PICU admission was calculated for assessing the severity of pneumonia. Results: The study found that the RISC score is a potentially useful tool for predicting severity and mortality risk in pediatric pneumonia patients. Conclusions: The findings may contribute to the development of more accurate and reliable scoring systems to guide appropriate treatment and improve outcomes in pediatric pneumonia patients.